Internalization Strategy of Moderation Value in Arabic Curriculum Development at Darus Salam Islamic Boarding School Jombang - Lailatul Qomariyah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Online learning has an impact on students' psychology, namely the decline in ethics, tolerance, and selfishness. This needs to be given a solution, namely through a strategy of internalizing the value of moderation in curriculum development in educational institutions where students study. This study aims to analyze how the strategy of internalizing the value of moderation in the Arabic curriculum at Darus Salam Islamic boarding school Jombang. This research uses a qualitative case study approach. Interviews, observations and documentation are techniques used by researchers in collecting data which are then analyzed by interactive analysis. The results of this study indicate that the strategy for internalizing the value of moderation in the development of the Arabic language curriculum at the Darus Salam Islamic Boarding School is through, 1) the Moderation Value Transformation Stage through the formulation and dissemination of the vision and mission of the Islamic boarding school, the integration of the Arabic language curriculum in Islamic boarding schools and in schools through the program. daily and weekly programs of Islamic boarding schools as well as information on student discipline in wall magazines and in Early Taaruf; 2) Value Transaction Stage, at this stage the value is moderated through good interaction between teachers and students or musyrif and students in implementing curriculum programs on learning activities and the material being studied; 3) Tran-internalization stage, at this stage the value of moderation is internalized through example and habituation. This research contributes to Arabic teachers in forming students who are moderate, tolerant and have character.